Interatrial Block Predicts Atrial Fibrillation and Total Mortality in Patients with Cardiac Resynchronization Therapy. (25th November 2020) - Jacobsson, J; Carlson, J; Reitan, C; Borgquist, R; Platonov, P.G
Abstract: Background: Interatrial block (IAB) and abnormal P-wave terminal force in lead V1 (PTFV1) are electrocardiographic (ECG) abnormalities associated with new-onset atrial fibrillation (AF) and death. However, their prognostic importance has not been proven in CRT recipients with advanced heart failure (HF). Purpose: To assess if IAB and abnormal PTFV1 are associated with new-onset AF or death in CRT recipients. Methods: CRT recipients without AF history before CRT implantation were included (n=210, median age 67 years, 80% male, 55% ischemic heart disease, 70% NYHA Class III/IV, median LVEF 25%, 51% CRT-P). Automated analysis of P-wave duration (PWD) and morphology classified patients as having either No IAB (PWD <120ms), Partial IAB (pIAB: PWD ≥120 ms, positive P waves in leads II and aVF) or Advanced IAB (aIAB: PWD ≥120 ms and biphasic or negative P wave in leads II or aVF). PTFV1 >0.04 mm·s was considered abnormal. Cox regression analyses adjusted for age, NYHA Class, ischemic etiology of HF, LBBB, LVEF and CRT-P vs. CRT-D were performed to assess the impact of IAB and abnormal PTFV1 on the primary endpoint new-onset AF, death or heart transplant (HTx) and the secondary endpoint death or HTx at 5 years of follow up. Results: IAB was found in 45% (34% pIAB and 11% aIAB) and was associated with both the primary (HR 1.9, 95% CI 1.2–2.9, p=0.004) and the secondary (HR 2.1, 95% CI 1.2–3.4, p=0.006) endpoints. Abnormal PTFV1 was not associated with outcome. See Forest plot for adjusted HRs for individual P-wave indices. Conclusions: IAB is associated with new-onset AF and death in CRT recipients and may be helpful in risk stratification in the context of HF management. Abnormal PTFV1 did not demonstrate any prognostic value in the setting of CRT-treated patients with advanced HF. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Swedish Heart and Lung Foundation